Alpha particle transmission coefficients from a global optical potential - Nicolis, N. G.; Papachristodoulou, C. A. (HNPS Advances in Nuclear Physics, 2020)
Statistical model calculations involving a large number of emitted particles can be greatly facilitated by using transmission coefficients in a parametrized form. Thus, the execution and storage of the results of extensive optical model calculations can be avoided. Along these lines, a parametrization of optical model transmission coefficients, involving n, p, 2H, 3He and 4He on many targets, was produced some years ago. In the present work, we question the validity of this technique in the description of low-energy alpha particle evaporation. We propose a new parametrization with an improved low energy behavior.